Metaphase II (MII) human oocytes with smooth endoplasmic reticulum clusters do not affect blastocyst euploid rate - Christine Shan-Chi Chiu; Tzu-Yu Hung; Ming-Huei Lin; Robert Kuo-Kuang Lee; Yu-Wen Weng; Yuh-Ming Hwu (Elsevier, 2022)
Objective: To investigate whether the rate of euploidy and pregnancy outcomes are affected by smooth endoplasmic reticulum clusters (SERc) and other metaphase II human oocyte dysmorphisms. Materials and methods: Retrospective analysis of the morphologies of metaphase II (MII) human oocytes, which had developed into 590 biopsied blastocysts derived from 109 patients that received preimplantation genetic testing for aneuploidies (PGT-A) cycles between March 2013 and December 2017. The euploid rate of blastocysts that originated from morphologically abnormal or normal oocytes were analyzed. The chromosome status of the blastocysts was determined and analyzed by array comparative genomic hybridization (aCGH) or next generation sequencing (NGS) following trophectoderm biopsy. Results: According to the odds ratios obtained for each oocyte morphotype, no statistically significant relationship was found between oocyte dysmorphisms and euploid rate. Specifically, although SERc-positive oocytes had a higher rate of arrest at two pronuclei, or 2 PN (26.7% vs. 19.4%, p > 0.05), the blastocyst formation rate was not affected as compared with SERc-negative oocytes (40.0% vs. 38.6%, p > 0.05). Among nine euploid embryos derived from oocytes with SERc, three single euploid embryo transfers were performed, of which one resulted in blighted ovum, and two resulted in the births of two healthy, singleton term babies. Conclusion: The results presented here suggest that oocyte dysmorphisms do not affect the euploidy rate of the blastocyst. The occurrence of SERc in the oocyte does not seem to impair the developing blastocyst nor does it interfere with good embryo formation rate and euploid rate. Thus, the embryos derived from SERc-positive oocytes could still be considered for embryo transfer if there are no other embryos available.